Consumers Perspectives on Adoption and Promotion of Millet-Based Products - S. Suganya; Dr. K. Rajamani; P.Annamalai (International Journal of Engineering and Management Research, 2024)
This study explores consumer attitudes towards millet-based foods and identifies strategies to enhance their market penetration. Findings reveal widespread awareness of millets and a positive perception of their health benefits. However, challenges such as limited availability and price sensitivity hinder widespread adoption. The research aims to analyse factors influencing consumer purchasing behaviour towards millet-based products, examining health outcomes and consumer satisfaction associated with these foods. Furthermore, it seeks to understand consumer preferences in the context of purchasing millet-based foods and snacks, thereby identifying emerging market opportunities in this sector. Recommendations include expanding educational efforts, improving distribution channels, emphasizing health benefits in marketing, offering competitive pricing, diversifying product offerings, and innovating new millet-based products. Addressing these recommendations can unlock the market potential of millet-based foods, promoting healthier diets and economic growth in the food industry. A total sample of 273 is taken from Consumers. The data have been collected using Structured Questionnaire. For the analysis purpose various tools are used such as Pie chart, Bar chart, Ranking, SPSS (Statistical Package for Social Sciences) technique such as Chi Square and Correlation are used.